2010
DOI: 10.1002/art.27504
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin signaling is crucial for joint destruction in experimental arthritis and is activated in osteoclasts from patients with rheumatoid arthritis

Abstract: Objective. Activation of the mammalian target of rapamycin (mTOR) pathway is important for immune cell activation and bone metabolism. To date, the contribution of mTOR signaling to joint inflammation and structural bone and cartilage damage is unknown. The aim of this study was to investigate the potential of inhibiting mTOR as a treatment of inflammatory arthritis.Methods. Human tumor necrosis factortransgenic mice in which inflammatory arthritis was developing were treated with 2 different mTOR inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 55 publications
4
113
0
7
Order By: Relevance
“…All these data underline the possible involvement of mTOR in cutaneous inflammatory diseases. Indeed, it is reported that mTOR is implicated in the development of several inflammatory and metabolic disorders, such as diabetes, metabolic syndrome, rheumatoid arthritis and Crohn's disease (11,12,(22)(23)(24)(25)(26)(27) (12). In addition, mTOR has been reported to be related to the triggering of Crohn's disease; indeed, mTOR plays a major role in the regulation of autophagy (23) the impairment of which represents a critical initiating point in this disease pathogenesis (24,25).…”
Section: Immunohistochemical Detection Ofmtor In: (A-b-c) Lesional mentioning
confidence: 99%
“…All these data underline the possible involvement of mTOR in cutaneous inflammatory diseases. Indeed, it is reported that mTOR is implicated in the development of several inflammatory and metabolic disorders, such as diabetes, metabolic syndrome, rheumatoid arthritis and Crohn's disease (11,12,(22)(23)(24)(25)(26)(27) (12). In addition, mTOR has been reported to be related to the triggering of Crohn's disease; indeed, mTOR plays a major role in the regulation of autophagy (23) the impairment of which represents a critical initiating point in this disease pathogenesis (24,25).…”
Section: Immunohistochemical Detection Ofmtor In: (A-b-c) Lesional mentioning
confidence: 99%
“…Кроме того, доклинические исследова-ния свидетельствуют о том, что блокирование mTOR при-водит к уменьшению размеров припухлости конечностей у грызунов и синовита при индуцировании артрита антиге-нами [154,155].…”
Section: сигнальный пу ть гексозаминаunclassified
“…Активность СПМТ обнаружена в синовиальной мем-бране больных ревматоидным артритом (РА), в частности в синовиальных остеокластах [155]. А пролиферация сино-виальных фибробластов, индуцированная тромбоцитар-ным ростовым фактором, у больных РА подавлялась при ингибировании mTOR рапамицином.…”
Section: сигнальный пу ть гексозаминаunclassified
See 1 more Smart Citation
“…It is likely that dysregulation of the mTOR-autophagy pathway may contribute too many human disorders including viral infections [22]. Inflammatory disorders [23,24] and cancer [25,26] and could be an attractive avenue for future therapeutic approaches [16]. The aim of the present work was to study the role of mTOR and autophagy in the progression of HCV-related liver disease.…”
Section: Introductionmentioning
confidence: 99%